GREEN SYNTHESIS NANOPARTIKEL GRAPHENE DENGAN AGEN PEREDUKSI URIN MANUSIA DAN APLIKASINYA SEBAGAI ADITIF BIONANOLUBRICANT BERBASIS CPO (CRUDE PALM OIL) - Irawan, Ahmad; Robiah, Robiah (Jurnal Distilasi, 2017)
Graphene is a nanomaterial that has been widely applied to various fields because of the uniqueness of the material, therefore this material is very interesting to be developed as an additive in lubricant. This study aims to determine the optimum additive weight ratio and obtain optimum operating conditions in the graphene dispersion process in base oil. This research is divided into 2 stages: preliminary research and main research. The preliminary study aims to transform the chemical structure of crude palm oil (CPO) through a three-stage reaction into a polyol as a base oil. The main research is the process of making bionanolubricant. Graphene is synthesized using a combination technique with a human urine as reducing agent. The formulations are known by varying the weight of the additive and the time of the dispersion. Variation of additive weight was 0% (A1), 0.25% (B1), 0.5% (C1), 1% (D1) while for dispersion time variation ranged from 0 min (A2), 60 min (B2), 90 minutes (C2) and, 120 minutes (D2). Based on the SEM-EDX test results, the SEM image formed graphene and spectrum layers on EDX show that the oxide in graphene has been successfully reduced. Bionanolubricant was tested for quality with 7 parameters. The composition of base oil formula 250 gr and graphene nanoparticles 0.5% w / w is the optimum additive weight ratio for C1 sample code whereas the economical dispersion time is 60 minutes. The result of the viscosity index test is 121,72, its pour point is 10,4oC, flash point equal to 228oC with lubrication capability tested through four ball tester got scar diameter equal to 0,87 mm. This Bionanolubricant belongs to the SAE 250 class and is classified as a GL-4 lubricant based on the quality level of API (American Petroleum Institute) performance test.